Izzivi pri načrtovanju knjižnične mreže splošnih knjižnic v mestnem okolju - Resman, Simona (Knjižnica, 2019)
Purpose: The paper discusses the contribution of the public library to urban environment identity, the value that the public library brings to the residents of the city and the specifics of positioning and planning of a library network in the urban environment. It is based on demographic and spatial data, which is combined with a spatial analysis of the library network. Methodology/approach: A review of professional literature and good practices on analysing and designing public library networks using the tools of geographic information systems (GIS) was carried out. Results: Based on the review, it is possible to determine whether the locations in the library network are appropriate. An overview of the toolkit was prepared, focusing on the GIS tools, through which we can store, manage and display the data. Thus, we can create visual caution maps that, on the one hand, represent the location of the library in the local environment, and at the same time, this will be the starting point for the evaluation of the library network and the implementation of its optimization. Research limitations: Regarding the size and the historical reasons, the Ljubljana City Library (LCL) network is very specific; therefore, we could only rely on foreign theoretical bases for planning the optimization of the library network, which is not transferable to the Slovenian library environment in all aspects. Originality/practical implications: The paper presents the theoretical starting points for carrying out the analysis and design of public library network optimization in the urban environment. Publicly available and free tools for obtaining the necessary data to build library support system with the help of GIS are presented
Keywords: informacijski sistemi; knjižnične mreže; Mestna knjižnica Ljubljana; splošne knjižnice